The Mulloon Rehydration Initiative: The project's establishment and monitoring framework. (31st January 2022) - Peel, Luke; Hazell, Peter; Bernardi, Tony; Dovers, Stephen; Freudenberger, David; Hall, Carolyn; Hazell, Donna; Jehne, Walter; Moore, Leah; Nairn, Gary
Abstract : The Mulloon Rehydration Initiative is a case study highlighting the challenges of integrating research into a catchment scale land‐repair project involving multiple landowners and partners. Starting with an innovative project in 2006 to install 'leaky weirs' on a single property, the project has now expanded to include stream rehabilitation works on 16 properties and aims to cover an area of 23, 000 ha of the Mulloon Creek, NSW and its main tributaries. Here, we describe the establishment phase of the project and the design of its monitoring framework.